Impact of capillary invasion on the prognosis of gastric adenocarcinoma patients: A retrospective cohort study - Xue, Lian (Oncotarget, 2016)
Capillary invasion (CI) has been found to play an important role in metastasis and recurrence of gastric adenocarcinoma (GAC). However, the prognostic significance of CI is still controversial. From January 2005 to December 2011, 1398 patients with GAC who underwent gastrectomy were retrospectively enrolled and divided into CI (+) and CI (−) groups. Clinicopathological features and survival outcomes were compared between these groups. In our study, 227 (16.2%) patients were CI (+). Patients with CI (+) had significantly more advanced tumors and worse prognosis than those with CI (−) (p < 0.001). CI was demonstrated as an independent prognostic factor (p = 0.023) in patients with GAC. When stratified by TNM stage, the prognosis of CI (+) group in stage III was remarkably worse than CI (−) group (p = 0.006), while the differences were not significant in stage I–II and stage IV (both p > 0.05). The nomograms indicated that CI was part of the individual prognostic prediction system. The predictive accuracy of CI and other characteristics was better than TNM alone (p < 0.001). Our finding suggested that CI was an independent prognostic factor in patients with GAC, and the nomogram based on CI and other clinicopathological factors was a valuable and accurate tool in individual prognostic prediction.